Analisis Pentashihan Surah Yasin dalam Kitab Imdad Karya Guru Sekumpul: Studi Perbandingan dengan Mushaf Standar Indonesia - nurjannah nurjannah (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The writing of Qur'anic mushaf in Indonesia has undergone a standardization process through the Indonesian Standard Mushaf (MSI) compiled by the Lajnah Pentashihan Mushaf Al-Qur'an (LPMQ). However, in various religious communities there are still forms of local mushaf used in Islamic practice, such as the Kitab Imdad by KH. Muhammad Zaini bin Abdul Ghani (Guru Sekumpul). This study aims to analyze the writing of Surah Yasin in Kitab Imdad and compare it with MSI, focusing on aspects of rasm, dhabṭ, waqaf signs, and other technical elements of writing. This research uses a qualitative approach with a comparative text study method. The results found ten technical differences between the writing of Surah Yasin in Kitab Imdad and MSI. These differences include the shape of certain letters (such as ro, mim, nun, and ha), the coloring system of lafaz that refer to Allah, the presence or absence of certain waqaf signs, and visual elements such as verse pieces at the bottom of the page. However, these differences are non-substantive and do not change the meaning of the verse. This shows that Kitab Imdad is a form of visual living Qur'an that lives in the midst of society, by maintaining the structure of the standard Mushaf but adapted to local pedagogical and aesthetic needs. Keywords: Pentashihan Mushaf, Indonesian standard mushaf, kitab imdad, guru sekumpul, surah Yasin